2006
DOI: 10.1111/j.1747-7379.2006.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Did House Members Vote for H.R. 4437?

Abstract: This article examines why members of the U.S. House of Representatives voted for H.R. 4437, the controversial 2005 bill to construct a 700‐mile immigration barrier along the U.S.‐Mexican border and to criminalize illegal presence and aid to undocumented immigrants. Logit analysis suggests that being a first‐term House member or a Republican and representing a district that was in the South or the West or heavily blue‐collar substantially boosted the odds of supporting H.R. 4437. If a member's district was disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 7 publications
5
30
0
Order By: Relevance
“…Both Gonzalez and Kamdar (2000) and Fetzer (2006) found that African-American district population was associated with more liberal voting patterns, although it was consistently insignificant in Gimpel and Edwards (1999) and largely insignificant in Wong (2006). 10 We therefore test this variable in our models.…”
Section: Politics Groups and Identitiesmentioning
confidence: 92%
See 2 more Smart Citations
“…Both Gonzalez and Kamdar (2000) and Fetzer (2006) found that African-American district population was associated with more liberal voting patterns, although it was consistently insignificant in Gimpel and Edwards (1999) and largely insignificant in Wong (2006). 10 We therefore test this variable in our models.…”
Section: Politics Groups and Identitiesmentioning
confidence: 92%
“…Gimpel and Edwards (1999) modeled House immigration votes from the 98 th to 104 th Congresses, finding that the share of foreign-born constituents was typically associated with more liberal votes. Other research has found that members with larger foreign-born constituencies were more likely to oppose the 1996 Immigration in the National Interest Act (Gonzalez and Kamdar 2000), and that Latino constituency share is associated with opposition to the 1984 Simpson-Mazzoli bill (Lowell, Bean, and de la Garza 1986) and the 2005 Sensenbrenner bill (Fetzer 2006). We therefore hypothesize that the Latino constituency share will be positively associated with comprehensive reform votes and negatively associated with restrictionist measures, although we will keep the racial threat possibility in mind.…”
Section: Politics Groups and Identitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…8 Models that include the term (Fetzer 2006;Casellas and Leal 2013) or gender (Fetzer 2006;Casellas and Leal 2013) of representatives do not substantively change the results. 9 Models that include the skill ratio of a district (Scheve and Slaughter 2001;Mayda 2006;Hainmueller and Hiscox 2010;Facchini and Steinhardt 2011) or poverty (Casellas and Leal 2013) rather than unemployment also do not substantively change the results.…”
Section: Resultsmentioning
confidence: 97%
“…4437 vote, Fetzer (2006) hypothesizes that, as reelection depends on the support of voters within a representative's district, "one would expect […] the demographics of a particular Congressional district to influence whether or not a given House member voted for H.R. 4437" (p. 699).…”
Section: Demographics and Partisanshipmentioning
confidence: 99%